The Pros and Cons of Sick Pay Schemes: A Method to Test for Contagious Presenteeism and Shirking Behavior - Stefan Pichler; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2015)
This paper proposes a test for the existence and the degree of contagious presenteeism and negative externalities in sickness insurance schemes. First, we theoretically decompose moral hazard into shirking and contagious presenteeism behavior. Then we derive testable conditions for reduced shirking, increased presenteeism, and the level of overall moral hazard when benefits are cut. We implement the test empirically exploiting German sick pay reforms and administrative industry-level data on certified sick leave by diagnoses. The labor supply adjustment for contagious diseases is significantly smaller than for non-contagious diseases, providing evidence for contagious presenteeism and negative externalities which arise in form of infections.
Keywords: I12; I13; I18; J22; J28; J32; 330; sickness insurance; sick pay; presenteeism; contagious diseases; infections; negative externalities; shirking